If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(g + 3) = -2(g + 31) Reorder the terms: 0.6(3 + g) = -2(g + 31) (3 * 0.6 + g * 0.6) = -2(g + 31) (1.8 + 0.6g) = -2(g + 31) Reorder the terms: 1.8 + 0.6g = -2(31 + g) 1.8 + 0.6g = (31 * -2 + g * -2) 1.8 + 0.6g = (-62 + -2g) Solving 1.8 + 0.6g = -62 + -2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '2g' to each side of the equation. 1.8 + 0.6g + 2g = -62 + -2g + 2g Combine like terms: 0.6g + 2g = 2.6g 1.8 + 2.6g = -62 + -2g + 2g Combine like terms: -2g + 2g = 0 1.8 + 2.6g = -62 + 0 1.8 + 2.6g = -62 Add '-1.8' to each side of the equation. 1.8 + -1.8 + 2.6g = -62 + -1.8 Combine like terms: 1.8 + -1.8 = 0.0 0.0 + 2.6g = -62 + -1.8 2.6g = -62 + -1.8 Combine like terms: -62 + -1.8 = -63.8 2.6g = -63.8 Divide each side by '2.6'. g = -24.53846154 Simplifying g = -24.53846154
| 24+3x=-45 | | .4x^2-1.1x=2 | | (2x^2+9x+4)=0 | | P+5=17 | | -4/5x-17=-10/3x-55 | | -14.4=-.6p | | 2x+10=x+0 | | 160/4= | | x^2+17X+49-3x=0 | | 21.5+.5x=50 | | X-3-15=12 | | 5x-(6x+2)=5x-20 | | X/3+2=9+4 | | -6x-4y=21 | | 2x-8=4y | | 180/3= | | 10x^2=11x+35 | | (5t+3)-2*(t+3)=29-5t | | 14y^2-19y+4=11y^2+11y-5 | | 6f-2=6f-2 | | 3/4=n | | -7-26=n | | 8p+6-7p= | | y^2-9y+15=0 | | 4-x=5x+28 | | 2(2x+22)=8x-20 | | 5q+4q= | | 6y-10=0 | | 14+8x=32+8x | | 2x=60-5x | | m-6/5+3.8=7-2m | | -j+5j+2=14 |